Electronic money and payments: Recent developments and issues - Ben Fung; Miguel Molico; Gerald Stuber (Bank of Canada, 2014)
The authors review recent developments in retail payments in Canada and elsewhere, with a focus on e-money products, and assess their potential public policy implications. In particular, they study how these developments will affect the demand for bank notes, and the central bank's balance sheet and its seigniorage revenue, which as a result might affect the central bank's ability to implement and conduct monetary policy and to promote financial stability. Other public policy issues, such as safety and efficiency, and user protection as well as legal, security and law enforcement, are also considered. While the demise of cash is not imminent, it is important for the central bank to continue to evaluate its potential roles with regard to e-money. – – Les auteurs analysent l'évolution récente des paiements de détail au Canada et à l'étranger, en se concentrant sur les produits de monnaie électronique, et évaluent leur incidence possible sur les politiques publiques. Plus particulièrement, ils étudient la façon dont les tendances observées influeront sur la demande de billets, ainsi que sur le bilan de la banque centrale et ses revenus de seigneuriage, ce qui pourrait avoir des répercussions sur la capacité de cette dernière de mettre en oeuvre sa politique monétaire et de promouvoir la stabilité financière. Ils examinent également d'autres enjeux des politiques publiques, notamment la fiabilité et l'efficience, ainsi que la protection de l'usager, la sûreté, l'application de la loi et des questions d'ordre juridique. Bien que la disparition de l'argent comptant ne soit pas imminente, il est impératif que la banque centrale continue d'évaluer les rôles qu'elle pourrait jouer dans l'utilisation de la monnaie électronique.
Keywords: E41; E42; 330; Banknotes; E-money; Financial services; Payment clearing and settlement systems; Billets de banque; Monnaie électronique; Services financiers; Systèmes de compensation et de règlement des paiements